Intelligent heterogeneous wireless network using machine learning techniques - Lim, Michelle Ming Min (Nanyang Technological University, 2021)
This project is concerned with optimizing performance of wireless BLE mesh network, tapping on machine learning techniques. The work involves algorithm development, test-bed implementation and testing using Python & C to optimize the network performance.